1995
DOI: 10.1111/j.1365-2958.1995.18050821.x
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of the genes encoding the haemolysin of Haemophilus ducreyi

Abstract: We previously identified a heat- and protease-labile haemolytic activity expressed by Haemophilus ducreyi. In order to characterize the haemolysin at the molecular level, genomic DNA from H. ducreyi was probed with haemolysin genes from other Gram-negative organisms. The haemolysin genes of Proteus mirabilis hybridized to H. ducreyi DNA suggesting that the haemolysin of H. ducreyi is related to the Proteus/Serratia pore-forming family of haemolysins. Tn916 mutagenesis was employed to isolate haemolysin-deficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
92
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(92 citation statements)
references
References 34 publications
0
92
0
Order By: Relevance
“…In Serratia marcescens, ShlB that belongs to the TpsB protein family has been shown to be essential for secretion and activation of the ShlA hemolysin (47). HpmB and HpmA in Proteus mirabilis (52), EthB and EthA in E. tarda (29), and HhdB and HhdA of H. ducreyi (39), which all belong to the TpsB and TpsA protein families, have the same functions (31). Furthermore, putative hemolysin genes were also identified in the Y. pestis genome.…”
Section: Discussionmentioning
confidence: 99%
“…In Serratia marcescens, ShlB that belongs to the TpsB protein family has been shown to be essential for secretion and activation of the ShlA hemolysin (47). HpmB and HpmA in Proteus mirabilis (52), EthB and EthA in E. tarda (29), and HhdB and HhdA of H. ducreyi (39), which all belong to the TpsB and TpsA protein families, have the same functions (31). Furthermore, putative hemolysin genes were also identified in the Y. pestis genome.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of FHA secretion is of particular interest, as despite its high efficiency it requires only one specific accessory protein, FhaC. It appears to be a distinct terminal branch of Sec-dependent secretion widely distributed among Gram-negative bacteria, as a growing number of FhaC homologs are being identified that are involved in the secretion of hemolysins or adhesins (5)(6)(7)(8).…”
mentioning
confidence: 99%
“…While the mechanism(s) by which this gram-negative bacterium causes genital ulceration remains to be determined (31), it has been established that this pathogen produces at least two toxins. The first of these is a cytotoxin with hemolytic activity (20,21); killing of human cells in vitro by this hemolysin requires direct contact between the bacterium and the eukaryotic cells (2,19). The other toxin can be detected by its activity in H. ducreyi culture supernatant fluid (26) and is a member of the cytolethal distending toxin (CDT) family (4,24).…”
mentioning
confidence: 99%